The Influence of Economic Literacy and Student Attitude on the Self-Concept Achievement of Business Students - Syahrul Nizam, Salam; Asmaul Husna, Haris Fadzilah; AMALINA, MURSHIDI; AL AMIRUL EIMER, RAMDZAN ALI; MUHAMMAD FAIRUZ, JAMIL; NUR AQILAH HAZIRAH, MOHD ANIM; TAK JIE, CHAN (URBE, 2024)
This study aims to identify the factors contributing to the self-concept achievement of business students. A survey questionnaire was employed as a research instrument to obtain quantitative data, involving a total of 402 respondents selected through random sampling. The data were analyzed using SPSS version 22.0 and Analysis of Moment Structures (AMOS). Descriptive and inferential analyses were conducted through parametric statistical tests, including t-tests and AMOS analysis. The t-test results showed no significant differences based on gender and location. AMOS analysis revealed that the level of economic literacy has a positive relationship with the self- concept of business students. The results also indicate that student attitude (SA) is at a high to moderate level and has a positive association with the self-concept of business students. Additionally, the analysis of the self-concept of business students (SCBS) also shows a high to moderate level. There is a significant correlation between economic literacy (EL) and student attitude (SA) toward achieving the self-concept of business students. The results also show a significant influence of the predictive factors, economic literacy (EL), and student attitude (SA), on the achievement of the self-concept of business students (SCBS). In conclusion, the researcher suggests emphasizing the self-concept of business students (SCBS), especially at the level of business subjects, to enhance achievement and academic performance, and facilitate students' transition to tertiary institutions at the university or college level. The factors EL and SA can provide advantages for students ready to pursue jobs requiring business-mindedness, which relates to their self-concept. By implementing these strategies, educators can support the personal growth and development of business students, equipping them with the skills, knowledge, and mindset needed to thrive in their academic and professional pursuits.